Photocatalytic Properties of ZnO Synthesized by Solid-State Combustion: Structural Analysis and Degradation of 4-Nitrophenol - Alejandro López, Alma Rosa; Serrano de la Rosa, Laura Elvira; Castillejos Mosqueda, Sandra Leticia; Cerna Cortez, Jorge; Silahua Pavon, Adib Abiu; Cervantes Uribe, Adrián; Martínez Gómez, Claudia (JOURNAL OF BASIC SCIENCES, 2025)
This study presents the synthesis and characterization of zinc oxide (ZnO) through solid-state combustion and its application in the photodegradation of 4-nitrophenol (4-NP). The obtained ZnO exhibited a hexagonal wurtzite crystal structure. UV-Vis spectroscopy revealed a band gap of 3.31 eV and a specific surface area of 0.63 m²/g. This zinc oxide demonstrated photocatalytic activity in the degradation of 4-nitrophenol (4-NP). These results show that solid-state combustion is an effective method for producing ZnO with optimal properties for environmental applications, without the need for additional chemical agents.